Theorising in mathematics education research: differences in modes and quality - Jablonka, Eva; Bergsten, Christer (NOMAD Nordic Studies in Mathematics Education, 2010)
In mathematics education research reports, we find a bewildering array of ”theories”, ”theoretical models” or ”theoretical frameworks”. The key notions and principles as well as the intellectual roots of these constructions are made more or less explicit, and the relations of theoretical entities to the empirical field under study are established in different ways. These differences imply discrepancies in quality. In this contribution we touch upon some of these issues. We attempt to show that an investigation of the relations between key concepts might help to read and evaluate theoretical underpinnings of research studies, and we argue that not all constructions that are labelled ”theoretical” meet the criteria we consider essential for productive theorising. We also allude to different modes of engaging with empirical material and different ways in which theories are used in research studies. The main part of our discussion is limited to examples of ”home-grown” theorising. The examples we have chosen to illustrate our points necessarily represent a biased selection.